Database-Based IP Network Routing - Pinto, Nelson Miguel Costa (2018)
The Software-Defined Networking (SDN) approach has the goal of simplifying network management. SDN uses a logically centralized approach to enable simpler network programmability and simplify the network architecture. SDN is in general associated with the OpenFlow protocol, which standardizes communication between a controller and network devices. Alternatively, a database approach could be used to tackle data exchange between controller and network devices. This solution requires the installation of a database server inside each switch, and replicas of those local switches databases, in the controller. The database approach offers several potential advantages over OpenFlow such as higher level of abstraction, flexibility and the use of mature implementations of standardised database protocols to propagate information events and commands. The purpose of this work is to apply a Database-Based Control Plane (DBCP) for SDN networks on a wide area environment. The objective is to implement a replacement of the control plane of a wide area network, currently achieved using a link-state protocol such as OSPF or IS-IS, by an SDN approach based on similar techniques as the ones used in [4]. We conducted an experiment, which we called IP-DBCP, that consisted of the definition of data models and the construction of an SDN network with database replication as the means of communication between one controller and multiple switches. To this end, a switch was developed, using OpenSwitch software as a logical hardware layer, that is capable of executing a MySQL database management system, load it with its characteristics and collect data related to its network neighbourhood. A controller was also developed that executes a MySQL database management system with the replicated databases of all switches. The controller uses those replicated databases to construct routing rules, using a shortest-path algorithm. Ultimately we tested the correct functioning of the solution and evaluated the convergence time by performing network state changes and compared the results with the ones found in traditional link state protocols.